Age of puberty and conception rates of Hungarian Merino, (Merino x Somali) F1 and (Merino x Barbados Blackbelly) F1 ewes - Gyimóthy, Gergely; Vass, Nóra; Balogh, Péter; Jávor, András; Kovács, András (Acta Agraria Debreceniensis, 2012)
The aim of our examination was to detect the puberty of the Hungarian Merino and its hairsheep crossbred ewes, and also to determine their average conception rates after having ram exposed in May and June. Hormon diagnostation was used to evaluate the exact date of the very first ovulation. Ultrasound technique was used for checking the conception rates of ewes. The pregnancy detection was applied after a month of the date of taking off the ram.We evaluated the ages of ewes at puberty. Statistical deviation and standard error were calculated. The results proved the Hungarian Merino x Somali (N=10), ((x ± s) = 173 ± 43) and also the Hungarian Merino x Barbados Blackbelly crossbred genotypes (N=7), ((x ± s) = 186 ± 19) have their puberty much earlier as compared to the fullbred Hungarian Merino ewes (N=10), ((x ± s) = 231 ± 95). We experienced the highest conception rate in the group of the (Hungarian Merino x Somali) F1 ewes after exposing the ram in the „out-of season” period of time.